Drawing Parallels from Aceh: Inclusive Governance as a Path to Resolving Sociopolitical Conflicts in South Sudan - Ceesay, Almamo; Asmorowati, Sulikah; Yarbou, Foday (POLITICO, 2025)
This research purpose in an effort to understand how inclusive governance could address the on going socio political conflict in South Sudan, this paper draws parallels from the Aceh peace process in Indonesia. Utilizing document review as the research method, the study analyzes peace agreements, government reports, and academic literature to identify key governance strategies that contributed to the stability and reconciliation in Aceh. Framed within the theoretical framework of inclusive governance, the paper highlights the role of power-sharing, local autonomy, and the participation of diverse stakeholders. This study contributes to the literature by offering a contextualized application of inclusive governance to South Sudan’s complex political landscape, providing recommendations for sustainable peace building efforts.